Living Lab Farm Area Building Design - Dara Wisdianti; Faurantia Forlana Sigit; Purwo Siswoyo; M. Aly Mujahidin (The International Conference on Education, Social Sciences and Technology (ICESST), 2023)
A living lab is an open innovation ecosystem in a real-life environment that uses an iterative feedback process across innovation lifecycle approaches to create sustainable impact. Living lab is an area that is projected to become a field laboratory and workshop center that accommodates all study programs at UNPAB. This area is also planned to become Ecoedutourism. This analysis resulted in the design of supporting buildings in the Al Amin Science and Industrial Park (Living Lab) farm area. The results of this design are expected to be a direction for the development of supporting buildings in the Farm area of Al Amin Science and Industrial Park (Living Lab).